Generation Z's Consumption and Savings Preferences Amidst Economic Uncertainty: A Thematic Analysis Approach - Hidayati, Rahma; Ardhini, Putri; Ashuratirana, Nurisnaini; Tanjung, Khairun Nisa; Sari, Nadia Atika; Nuraya , Ahmad Setiawan (Jurnal Ilmu Manajemen dan Ekonomika, 2025)
This study explores the consumption behaviour and savings preferences of Generation Z Indonesia (aged 17-25 years) in the face of global economic uncertainty using a qualitative approach through in-depth interviews. The results show a duality of behaviour, where the majority of respondents have an awareness of saving for emergency funds or investment, but the consistency of saving is hampered by irregular income and a consumptive lifestyle influenced by social media as a source of information as well as a trigger for impulsive consumption. Additional quantitative data reveals that 63% of respondents allocate more than 30% of their income to lifestyle, while 57% actively use digital investment apps. This research emphasizes the importance of digital financial literacy and consumption behaviour education as strategies to create more adaptive and sustainable financial management among Generation Z and recommends the integration of financial literacy in the education curriculum and protective regulation of digital financial platforms.